2019
DOI: 10.3892/ol.2019.10927
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed microRNAs and the potential of microRNA‑455‑3p as a novel prognostic biomarker in glioma

Abstract: Glioma is an aggressive central nervous system malignancy. MicroRNAs (miRNAs/miRs) have been reported to be involved in the tumorigenesis of numerous types of cancer, including glioma. The present study aimed to identify the differentially expressed miRNAs in glioma, and further explore the clinical value of miR-455-3p in patients with glioma. GEO2R was used for the identification of the differentially expressed miRNAs according to the miRNA expression profiles obtained from the Gene Expression Omnibus databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…In addition, in the results of an expanded study on lower grade glioma, more statistically significant genes were found. There were reports with findings consistent with those of ours on hsa-miR-1262, hsa-miR-455-3p, LPAL2 [83][84][85][86], and some reports even contradicted our findings on hsa-miR-204-5p and hsa-miR-197-3p [87,88]. Although related studies are still insufficient, the previous report about hsa-miR-186-5p in glioblastoma contradicted our findings [89].…”
Section: Discussionsupporting
confidence: 63%
“…In addition, in the results of an expanded study on lower grade glioma, more statistically significant genes were found. There were reports with findings consistent with those of ours on hsa-miR-1262, hsa-miR-455-3p, LPAL2 [83][84][85][86], and some reports even contradicted our findings on hsa-miR-204-5p and hsa-miR-197-3p [87,88]. Although related studies are still insufficient, the previous report about hsa-miR-186-5p in glioblastoma contradicted our findings [89].…”
Section: Discussionsupporting
confidence: 63%
“… 26 However, in glioma patients, the miRNA was noted to be significantly upregulated, and an increasing expression of this miRNA was associated with decreasing five-year overall survival rates. 27 The specific mechanism of miR-455-3p, with respect to PAAD, is still unclear. Therefore, further studies on the expression and mechanism of miR-455-3p may assist in examining it as a potential early biomarker and tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR-455 has been proposed as a cancer biomarker and it may be involved in the etiology of cancer. Wang et al 18 reported that in patients with glioma, miR-455-3p was significantly upregulated and according to Liu et al 19 , miR-455-3p elicited aberrant up-regulation in various human cancer types and was significantly associated with the lower overall survival of cancer patients. Moreover, Liu et al 20 found that miRNA455-3p promotes the invasion and migration of targeting tumor suppressor etoposide-induced 2.4 and suggested that it might be a potential prognostic biomarker and a therapeutic target in patients with triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%